Pengaruh perminyakan terhadap pengecatan dasar - Susanto, Heru Budi; Widowati, Titik Purwati; Hasan B, Hasan B (Majalah Kulit, Karet, dan Plastik, 1997)
The aim of this experiment was to evaluate the effects of the fatliquor agents on the color of the crust. Materials used on this experiment were 30 pieces of half skin, grade I â II with 0.6 â 0.7 mm in their thickness. Two types of fatliquor agents used in this experiment, there were synthetic (MI) and natural fatliquor agents (M2). Each fatliquor agents were 12% (w/w) on shave weight and dye use 2% (w/w)) on cruct weight. The results of this experiment showed that the type of fatliquor agents used influence the color of the dyed crust. All the color of the crust using natural fatliquor are darker (3,6 ; 4,5 and 5) than that one using synthetic fatliquor and control. However, the rubfastness (dry and wet) of crust using the synthetic fatliquor (4,22 and 4,44) better than that one using natural oil (3.67 and 3.34).